WIPO Technology Trends 2019: Artificial Intelligence - Executive Summary. - World Intellectual Property Organization (World Intellectual Property Organization, 2019)
WIPO Technology Trends 2019: Artificial Intelligence documents how AI-powered technologies are rapidly entering global markets and brings together viewpoints from experts at the cutting edge of AI. It is a contribution that aims to provide decisionmakers in the public and private sectors with an improved knowledge base for discussions on the future of AI and the policy and regulatory framework for this fast-moving area.